Implementation of PDAM Tirtanadi Risk Management Information System With Enterprise Risk Management (ERM) Approach - Widodo, Mhd. Aria Agung; Putri, Raissa Amanda (Green Publisher Indonesia, 2025)
PDAM Tirtanadi plays a role in providing clean water in North Sumatra. This research aims to apply Enterprise Risk Management (ERM) to improve the operational risk management of PDAM Tirtanadi, as well as designing a web-based pipe and water flow risk management system. The research methodology uses R&D with risk identification, risk color level, and COSO documents. By implementing an ERM-based Operational Risk Management Information System, PDAM Tirtanadi is expected to significantly improve its operational resilience. This will enable the company to anticipate and mitigate risks before they have a serious impact, thereby minimizing service disruptions and financial losses. Hopefully, this approach will result in increased operational efficiency, reduced costs, and improved customer satisfaction.